Silent Resistance Against Patriarchy in Two Short Stories by Yiyun Li and Ni Komang Ariani - Muhammad Ilham Ali; Olga Anneke Rorintulus; Michelle Rachel Lontaan (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2025)
This article explores the theme of women’s silent resistance against patriarchal oppression as depicted in Yiyun Li’s A Flawless Silence and Ni Komang Ariani’s Sepasang Mata Dinaya yang Terpenjara. Through a comparative literary analysis, the study examines how silence becomes a strategic form of resistance employed by the female protagonists Min and Dinaya who navigate the constraints of patriarchal expectations within their respective cultural settings. Rather than interpreting silence as submission, this article highlights how both characters use silence to assert agency, preserve identity, and subtly challenge the power structures that confine them. Central to this analysis are the interwoven themes of domestic constraint, cultural expectation, and psychological endurance, which shape the characters’ experiences and strategies of resistance. The study contributes to discussions on women’s narratives of struggle and resilience, offering insights into how literature portrays quiet defiance as a meaningful response to gender-based oppression.